Administrasi Pelaksanaan Pendidikan Inklusi Pada Lembaga Pendidikan Islam - Rieskha Tri Adillah EM; Uswah Khairani; Athifa Khalisha Majri; Fatimah Marzuqoh; Wismanto Wismanto (Harmoni Pendidikan : Jurnal Ilmu Pendidikan, 2024)
This research explains research on the management of the implementation of inclusive education in Islamic educational institutions. The aim of this research is to reveal the ABK service system that is integrated with formal education services. The method used in this research uses a library research method or approach, where library research can be understood as a series of activities related to data collection methods, reading, recording and processing library research materials. The results of this research show that inclusive education as a ABK service system is integrated with formal education services, the existing problems and solutions provided include; Inclusive Education is equated with National School Education, Procedures for resolving problems faced by Schools in Carrying out Inclusive Education, Implementation of Inclusive Schools at Islamic Education Institutions, Policies and Solutions for Handling Problems that Occur in Schools that Cover Inclusive Education.